Theoretical aspects of educational services and distance education in the context of transition to the digital economy - Yusupov Nurbekjon Hasan ogly, (THE INNOVATION ECONOMY, 2026)
The article examines the main economic and social factors influencing the growth of the e-commerce market in Uzbekistan. Economic, social and technological aspects contributing to the growth of the online market based on existing e-commerce facilities in the country were analyzed. The activities of popular trading platforms in Uzbekistan were also analyzed and proposals for their further development were developed